Amyloid A Amyloidosis After Renal Transplantation: An Important Cause of Mortality. Issue 8 (August 2020) - Sarihan, Irem; Caliskan, Yasar; Mirioglu, Safak; Ozluk, Yasemin; Senates, Banu; Seyahi, Nurhan; Basturk, Taner; Yildiz, Abdulmecit; Kilicaslan, Isin; Sever, Mehmet Sukru
Abstract : Background: There are limited data on the outcome of transplant recipients with familial Mediterranean fever (FMF)-associated AA amyloidosis. The aim of the present study is to evaluate demographic, clinical, laboratory, and prognostic characteristics and outcome measures of these patients. Methods: Eighty-one renal transplant recipients with FMF-associated AA amyloidosis (group 1) and propensity score–matched transplant recipients (group 2, n = 81) with nonamyloidosis etiologies were evaluated in this retrospective, multicenter study. Recurrence of AA amyloidosis was diagnosed in 21 patients (group 1a), and their features were compared with 21 propensity score–matched recipients with FMF amyloidosis with no laboratory signs of recurrence (group 1b). Results: The risk of overall allograft loss was higher in group 1 compared with group 2 (25 [30.9%] versus 12 [14.8%]; P = 0.015 [hazard ratio, 2.083; 95% confidence interval, 1.126-3.856]). Patients in group 1 were characterized by an increased risk of mortality compared with group 2 (11 [13.6%] versus 0%; P = 0.001 [hazard ratio, 1.136; 95% confidence interval, 1.058-1.207]). Kaplan-Meier analysis revealed that 5- and 10-year patient survival rates in group 1 (92.5% and 70.4%) were significantly lower than in group 2 (100% and 100%; P = 0.026 and P = 0.023, respectively). Although not reaching significance, overall, 5- and 10-year graft survival rates (57.1%, 94.7%, and 53.8%, respectively) in group 1a were worse than in group 1b (76.2%, 95%, and 77.8%, respectively; P = 0.19, P = 0.95, and P = 0.27, respectively). Conclusions: AA amyloidosis is associated with higher risk of mortality after kidney transplantation. Inflammatory indicators should be monitored closely, and persistent high levels of acute-phase reactants should raise concerns about amyloid recurrence in allograft.